Moderate Exercise Allows for shorter Recovery Time in Critical Limb Ischemia - Lejay, Anne; Laverny, Gilles; Paradis, Stéphanie; Schlagowski, Anna-Isabel; Charles, Anne-Laure; Singh, François; Zoll, Joffrey; Thaveau, Fabien; Lonsdorfer, Evelyne; Dufour, Stéphane; Favret, Fabrice; Wolff, Valérie; et al. (Frontiers in physiology, 2017)
Whether and how moderate exercise might allow for accelerated limb recovery in chronic critical limb ischemia (CLI) remains to be determined. Chronic CLI was surgically induced in mice, and the effect of moderate exercise (training five times per week over a 3-week period) was investigated. Tissue damages and functional scores were assessed on the 4th, 6th, 10th, 20th, and 30th day after surgery. Mice were sacrificed 48 h after the last exercise session in order to assess muscle structure, mitochondrial respiration, calcium retention capacity, oxidative stress and transcript levels of genes encoding proteins controlling mitochondrial functions (PGC1α, PGC1β, NRF1) and anti-oxidant defenses markers (SOD1, SOD2, catalase). CLI resulted in tissue damages and impaired functional scores. Mitochondrial respiration and calcium retention capacity were decreased in the ischemic limb of the non-exercised group (V = 7.11 ± 1.14 vs. 9.86 ± 0.86 mmol 02/min/g dw, < 0.001; CRC = 7.01 ± 0.97 vs. 11.96 ± 0.92 microM/mg dw, < 0.001, respectively). Moderate exercise reduced tissue damages, improved functional scores, and restored mitochondrial respiration and calcium retention capacity in the ischemic limb (V = 9.75 ± 1.00 vs. 9.82 ± 0.68 mmol 02/min/g dw; CRC = 11.36 ± 1.33 vs. 12.01 ± 1.24 microM/mg dw, respectively). Exercise also enhanced the transcript levels of PGC1α, PGC1β, NRF1, as well as SOD1, SOD2, and catalase. Moderate exercise restores mitochondrial respiration and calcium retention capacity, and it has beneficial functional effects in chronic CLI, likely by stimulating reactive oxygen species-induced biogenesis and anti-oxidant defenses. These data support further development of exercise therapy even in advanced peripheral arterial disease.